Understanding BRCA Mutation Carriers' Preferences for Communication of Genetic Modifiers of Breast Cancer Risk. Issue 4 (3rd April 2019) - Hovick, Shelly R.; Tan, Naomi; Morr, Lindsey; Senter, Leigha; Kinnamon, Daniel D.; Pyatt, Robert E.; Toland, Amanda E.
Abstract : Refined estimates of risk based on genetic risk modifiers could assist BRCA mutation carriers in understanding their risk, but it is not clear whether carriers are interested in receiving these estimates or how they might benefit from them. Using qualitative interviews, we investigated female BRCA 1 and BRCA 2 mutation carriers' (N = 20) reactions to numerical and verbal presentations of breast cancer risk based on risk modifiers and assessed women's preferences regarding visual formats for communicating risk. Our results show carriers are interested in receiving refined risk estimates and suggest the estimates may influence decision-making regarding cancer prevention, depending on the nature of the risk assessment. Although accurate and precise estimates of breast cancer risk are most important to women, they preferred quantitative risk estimates expressed as a proportion with or without a population comparison; however, women noted that comparisons to other BRCA mutation carriers were less useful given their high risk. Participants also preferred communication of a risk as a specific percentage versus a range of risk, but a clear preference regarding visual displays was not expressed. Results support many existing recommendations for genetic risk communication and provide guidance for the development of tools incorporating genetic risk modifiers.